Broiler Chickens On-Farm Welfare Assessment: Estimating the Robustness of the Transect Sampling Method - BenSassi, Neila; Averós, Xavier; Estevez, Inma (Frontiers in Veterinary Science, 2019)
Assessing commercial broiler chickens´ welfare usually comes at the cost of reduced precision due to the large flock sizes and required time commitments. The transect method for on-farm welfare assessment is conducted by walking within delimited paths between feeder and drinker lines within the commercial house, referred to as transects. This non-invasive method is conducted by detecting birds with signs of impaired welfare indicators, which include: leg problems, sickness, body wounds, and feather dirtiness. The transect method has been validated for commercial turkey flocks but not for broiler chickens due to the large flock sizes. The aim of this study was to evaluate the robustness of the transect method in broiler chicken flocks through a capture-recapture approach of a known subpopulation of 80 birds. Groups of 10 chickens were captured and individually marked in eight locations of the house. Two observers collected the number and position of the detected marked birds while walking along non-adjacent transects (4 samplings/house/day) during the two following days. Detection and repetition rates per house, and within transects were calculated, as well as the effects of flock density, transect number/house (6 vs 8) and sampling time (morning vs afternoon). The number of traveled transects was calculated for birds detected more than once and the population random distribution was tested by comparing the number of observed and expected birds/transect. Results showed more than 64% of detection rate with a repetition rate/house sampling of 24% and per transect of 1.66%. Higher repetition rates in six-transect houses and during morning samplings were detected. The number of traveled transects was higher in eight-transect houses and from birds first detected at walls, indicating longer traveled distances in wider houses. In addition, bootstrapping techniques were used to calculate the optimal sampling effort. Our findings indicate that the lowest repetition rates and optimal sampling can be achieved by assessing two transects, being one wall and one central, separated by three transects in between. Such sampling procedure would provide robust results for welfare assessment of commercial broiler chicken flocks.